An investigation of the effect of technological conditions of knitting on the structural characteristics of elastic fabric for compression cover - Кизимчук, О. П.; Мельник, Л. М.; Галавська, Л. Є.; Кйосев, Й.; Арабулі, А. Т.; Садретдінова, Н. В. (Fashion Industry, 2026)
Purpose. The paper aims to study both the linear dimensions and structural parameters (fabric density, thickness, surface density, wales and courses spaces) of elastic weft-knitted fabrics used in the manufacture of compression products. The purpose of the work is to establish the influence of the interlooping repeat and technological parameters of knitting (sinker depth of the ground structure and tension of bent weft thread) on the studied indicators. Methods. Standard methods were used for specimens’ preparation and for test structural parameters and physical properties of elastic weft knitted fabric. Results. It has been established that changing the repeat for the bent-weft elastomeric thread decisively affects the linear dimensions of the knitted tubes (especially width) and the fabric`s structural characteristics. With the bent weft thread at every third needle, the fabric became denser by 8-10%, narrower by 5-9%, shorter by 3-9%, thicker by 10-20%, and heavier by 6-16% compared to the fabric with the bent weft thread at every third needle. Simultaneously, increasing the feed speed of the bent weft thread decreases the number of wales per 100 mm and, therefore, determines the width of the future knitted product. Adjusting the density of the ground structure affects the number of courses per 100 mm and the fabric`s thickness. An increase in the value within the experiment leads to a 20-25% increase in the number of courses per 100 mm and a 22-30% decrease in the fabric`s thickness. The scientific novelty of the work. The main factors influencing the structure and linear dimensions of elastic knitted fabric have been identified, and the recommended levels of input knitting parameters have been established in this study. It allows varying the material's properties to design improved compression products. Practical significance. The results obtained serve as a basis for improving the manufacturing process of compression products for patients after limb amputation. Taking into account factors related to limb shape and the level of amputation, it is possible to adjust the material's structural and mechanical properties during product manufacturing, thereby providing the necessary physiotherapeutic effect.